Reconstruction of Consumer Protection Law in the Digital Era: A Legal Responsiveness Perspective - Haryanti, Tuti (Faculty of Law, Universitas Pekalongan, 2025)
Law Number 8 of 1999 concerning Consumer Protection (UUPK) has served as the legal foundation for consumer protection in Indonesia for over two decades. However, in practice, various issues continue to arise, particularly concerning the misalignment between existing regulations and the rapid development of digital technology, the complexity of electronic transactions, and the weak enforcement mechanisms against business actors. This article aims to examine the urgency of reconstructing the UUPK through the lens of the theory of legal responsiveness, which emphasizes the adaptability of law to social and economic dynamics. This study employs a normative juridical method with a conceptual and legislative approach. The novelty of this study lies in its theoretical perspective, using legal responsiveness as the basis for proposing reforms to the UUPK, rather than merely offering normative-technical corrections. The findings suggest that reforming the UUPK must address institutional structures, the expansion of digital consumer rights, and the strengthening of enforcement through administrative sanctions and digital governance instruments. The conclusion recommends a comprehensive redrafting of the UUPK to make it more responsive to social, technological, and economic changes, and aligned with adaptive and progressive principles of universal consumer protection.